Antimicrobial and Analgesic Effect of Dhoopana with Sriveshtakadi Choorna in Non-Healing Ulcer - A Case Study (International Journal of Ayurveda and Pharma Research, 2023)
A chronic ulcer may be defined as one that fails to heal in the expected time for a ulcer of that type, which is usually less than 3 weeks. Chronic ulcers usually respond slowly to conventional treatments. In Ayurveda classics, ulcers its types and management has been explained. Signs and symptoms of non-healing ulcers can be compared with features of Dushtavrana. In spite of the modern advances that have been made; the management of Chronic ulcer is still a challenge for the clinician. Sushruta was quite aware of the importance of ulcer management. 60 methods of treatment of Vrana have been explained in Susruta Samhita Chikitsa stana Dvivraneeya adhyaya and one among them is Dhoopana. Dhoopana is indicated in ulcers which have predominance of Vata, severe pain and exudation. In Susruta Samhitha suthrasthana Misraka adhyaya, Dhoopana with Sriveshtaka, Sarjarasa, Sarala, Devadaru and other Sara-vrikshas are explained. In the present case study, 60 year old male patient who visited OPD with non-healing ulcer over left side of left lower limb with pain and purulent discharge from the ulcer was subjected to Dhoopana for 7 days twice daily for 10 minutes with Sriveshtakadi dhoopa choorna. Assessment of pain was done with VAS and VRS scale, discharge was assessed with grading scale and microbial content was assessed with Pus culture. After the study period there was considerable relief of pain and discharge. The organism Staphylococcus aureus present in initial swab was absent after 7 days of Dhoopana.